2004
DOI: 10.1023/b:rubi.0000030127.46845.f0
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Semax, ACTH 4–10 Heptapeptide, to Plasma Membranes of the Rat Forebrain Basal Nuclei and Its Biodegradation

Abstract: The binding characteristics of the peptide Semax (Met-Glu-His-Phe-Pro-Gly-Pro) to plasma membranes of basal nuclei of the rat forebrain and the dynamics of its degradation during its incubation with these membranes were studied. Binding of the homogeneously labeled [G-3H]Semax was shown to be time-dependent, specific, and reversible. Specific binding of the heptapeptide depended on calcium ions and was characterized by the dissociation constant of the ligand-receptor complex Kd = 2.41 +/- 1.02 x 10(-9) M and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Subsequently, it was demonstrated in vivo that Semax application increases both protein and mRNA levels of Bdnf, and TrkB, and mRNA level of Ngf in rat hippocampus (Dolotov et al 2006;Agapova et al 2007). At the same time, the studies of Semax degradation in rat serum and its entry to the rat brain (Potaman et al 1991(Potaman et al , 1993Dolotov et al 2004) and the studies of self-maintained effects of PGP and other proline-containing peptides (Lyapina et al 2000;Samonina et al 2001;Zhuikova et al 2003;Storozhevykh et al 2007) raise the question of whether C-terminal PGP tripeptide contributes to the effects of Semax. Recently we reported that both Semax and PGP affected the mRNA expression of some growth factors and their receptor genes under conditions of an experimental focal cerebral ischemia in rats (Dmitrieva et al 2008b).…”
Section: Introductionmentioning
confidence: 96%
“…Subsequently, it was demonstrated in vivo that Semax application increases both protein and mRNA levels of Bdnf, and TrkB, and mRNA level of Ngf in rat hippocampus (Dolotov et al 2006;Agapova et al 2007). At the same time, the studies of Semax degradation in rat serum and its entry to the rat brain (Potaman et al 1991(Potaman et al , 1993Dolotov et al 2004) and the studies of self-maintained effects of PGP and other proline-containing peptides (Lyapina et al 2000;Samonina et al 2001;Zhuikova et al 2003;Storozhevykh et al 2007) raise the question of whether C-terminal PGP tripeptide contributes to the effects of Semax. Recently we reported that both Semax and PGP affected the mRNA expression of some growth factors and their receptor genes under conditions of an experimental focal cerebral ischemia in rats (Dmitrieva et al 2008b).…”
Section: Introductionmentioning
confidence: 96%
“…At the same time currently there are no data on the participation of the known MCRs in the implementation of the nootropic effect (Hoogduijn et al 2002, Hruby et al 2011. Therefore, to date, the question of the action of ACTH analogs through MCRs is still open, and it is assumed that there is at least one more undescribed subtype of receptors, through binding to which their nootropic effects can be realized (Dolotov et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The same authors performed a genome‐wide analysis of changes in rat brain transcriptome under the influence of PGP in pMCAO conditions 79 . Because the PGP peptide is one of the predominant derivatives of Semax in the blood plasma and brain tissue of animals, 80 it could be expected that the observed effects of Semax and PGP would be similar. However, as mentioned above, the influence of PGP on the expression levels of genes encoding growth factors only partially coincided with that of Semax 76 .…”
Section: Transcriptomic Studies Of Regulatory Peptides In Experimentamentioning
confidence: 99%